ETHNO-MEDICINAL PLANTS AND METHODS USED BY GWANDARA TRIBE OF SABO WUSE IN NIGER STATE, NIGERIA TO TREAT MENTAL ILLNESS - Ibrahim, Jemilat Aliyu; muazzam, Ibrahim; Jegede, Ibikunle Adeola; Kunle, oluyemisi F; Okogun, Joseph I (African Journal of Traditional, Complementary and Alternative Medicines, 2006)
The Gwandara people of Sabo Wuse in Niger State, Nigeria are the original inhabitants of Wuse in Abuja Municipal Area Council. They were resettled at this present location of Sabo Wuse from Wuse in the Federal Capital Territory Abuja when the seat of government moved from Lagos to Abuja 30 years ago. Sabo Wuse still remains relatively a remote settlement and their lifestyle unchanged. They still depend on a large extent on their traditional knowledge of medicinal plants to treats ailments. Ethnobotanical survey was conducted to identify and document methods traditionally utilized for treatment of mental illness and to expand the quality and quantity of information for research and development especially in the area of new drug discovery and development. About Sixty seven (67) traditional medicine practitioners were interviewed orally with use of questionnaire. From our survey, various methods were found to be used by the traditional medicine practitioners to treat mental illness and associated disorders. These include music, incantations and medicinal plants in various formulations – decoction, powder, infusion –, which are administered in various ways like fumigation, inhalation, bathing, steaming and drinking. Eighteen plant species belonging to twelve different families were documented to be included in these therapies. In conclusion, there is an array of plants used locally to treat mental illness and it is recommended that such surveys should be funded and leads for drugs to treat mental illness obtained from such, at the same time documenting our indigenous knowledge.